Leader-Follower Formation and Obstacle Avoidance for Nonholonomic Mobile Robots Using Velocity Obstacles - Putra, Misbah Habib; Agustinah, Trihastuti; Sahal, Mochammad (JAREE (Journal on Advanced Research in Electrical Engineering), 2025)
A multi-robot system is a group of robots that coordinate and perform complex tasks with the help of a communication system. The commonly adapted approaches in multi-robot formation control include the leader-follower method, where the leading robot acts as the coordination center, and follower robots track the movement of the leading robot. Multi-robot formations are usually faced by static and dynamic obstacles in the operational environment. In this paper, the obstacle-avoidance challenge is tackled by adopting the concept of velocity obstacles in a way that enables the robots to efficiently consider not only the velocity of an obstacle but also its direction in order to avoid collision. The method is evaluated through several simulation scenarios in different environments. The simulation results show that the multi-robot formation version can successfully avoid static and dynamic obstacles and reform a formation right afterward from zero collisions.